PERANAN SISTEM AKUNTANSI MANAJEMEN TERHADAP PENGENDALIAN KUALITAS PRODUK - ., LAULINDA (: 2303-1719)
In the business world increasingly fierce competition, companies are required to make a good quality product. SAM is the formal procedures and systems that use information to maintain and provide an alternative to the various activities of the company. In SAM, there are four characteristics: broad scope, aggregation, integration and timeliness. Product quality control is an effective system for integrating the activities of maintenance and development of quality within an organization so as to obtain production and service in the most economical and satisfying consumers. In controlling the quality of the product, there are three components of the SAM is quality control goals, quality feedback, and quality incentives. Companies must exercise control over the resulting product to minimize the production of a defective or damaged products. All the information can be presented using the SAM to determine the condition of product quality and performance of the production employees in producing goods. Companies that implement SAM will be able to manage both the data into information so that it can present a report. The report is used to help managers to take a decision.